PERAN PEMBELAJARAN TARI DALAM MENGEMBANGKAN KECERDASAN KINESTETIK DAN KARAKTER SISWA - Qamarudin, Ali; Nurharini, Atip (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the role of dance extracurricular learning in developing kinesthetic intelligence and shaping student character at SDN 2 Trompo, Kendal District, Kendal Regency, Central Java. A descriptive qualitative approach was employed using field research methods conducted from December 2025 to January 2026. Data were collected through structured interviews, non-participant observation, and documentation, then analyzed using Miles and Huberman's interactive model with source and technique triangulation to ensure data credibility. The findings reveal that dance extracurricular activities significantly contribute to the development of five aspects of kinesthetic intelligence, namely movement coordination, body balance, flexibility, movement accuracy, and motor memory. The dance learning process also fosters four student character values, including self- confidence, discipline, responsibility, and cooperation and mutual assistance. A key finding of this study is that both aspects develop simultaneously and are integrated throughout every stage of learning, from the introduction of basic movements to performance experiences before an audience.